2013
DOI: 10.4137/jen.s12958
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms at the Basis of Plasticity in the Developing Visual Cortex: Epigenetic Processes and Gene Programs

Abstract: Neuronal circuitries in the mammalian visual system change as a function of experience. Sensory experience modifies neuronal networks connectivity via the activation of different physiological processes such as excitatory/inhibitory synaptic transmission, neurotrophins, and signaling of extracellular matrix molecules. Long-lasting phenomena of plasticity occur when intracellular signal transduction pathways promote epigenetic alterations of chromatin structure that regulate the induction of transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 108 publications
3
12
0
Order By: Relevance
“…This closure correlates with the formation of PNNs. PNNs are reticular structures that result from the aggregation of ECM macromolecules around the proximal neurite and cell body, particularly around inhibitory GABAergic parvalbumin-expressing interneurons whose maturation is one of the factors controlling plasticity (Hensch, 2005;Maya-Vetencourt and Pizzorusso, 2013). A reduction in PNNs number is also associated with schizophrenia (Berretta et al, 2015).…”
Section: Role Of Glycosaminoglycan and Proteoglycans In Neuroplasticitymentioning
confidence: 97%
“…This closure correlates with the formation of PNNs. PNNs are reticular structures that result from the aggregation of ECM macromolecules around the proximal neurite and cell body, particularly around inhibitory GABAergic parvalbumin-expressing interneurons whose maturation is one of the factors controlling plasticity (Hensch, 2005;Maya-Vetencourt and Pizzorusso, 2013). A reduction in PNNs number is also associated with schizophrenia (Berretta et al, 2015).…”
Section: Role Of Glycosaminoglycan and Proteoglycans In Neuroplasticitymentioning
confidence: 97%
“…Interestingly, miRNA-132/212 also act on the synaptic plasticity of visual cortex [ 60 62 ]. It has been found that monocular deprivation would be in a position to hinder the modification of miRNA-132/212 locus and subsequently decreased the miRNA-132/212 cluster transcription in developing visual cortex [ 60 ].…”
Section: Regulation Of Mirna-132 In Synaptic Plasticitymentioning
confidence: 99%
“…Likewise, parallel findings revealed that the expression of miRNA-132 in the visual cortex was upregulated by light stimulation and delayed in response to dark-rearing. Inhibition of miRNA-132 can prevent dendritic spine maturation, ocular dominance plasticity, and formation of synaptic connectivity in vivo [ 61 , 62 ].…”
Section: Regulation Of Mirna-132 In Synaptic Plasticitymentioning
confidence: 99%
“…34 Experience-dependent modifications of the neuronal circuitries implying neuroplasticity were demonstrated in the mammalian and rodent visual systems. Proposed mechanisms include epigenetic alteration of chromatin structure, leading to modification of synaptic connectivity and neural circuitry in the mammalian striate cortex 35,36 and remodeling of neuronal pathways. 36,37 Impact of Visual Field Defects…”
Section: Natural History Of Retrochiasmal Visual Field Defectsmentioning
confidence: 99%